A field study to evaluate side-to-side differences in the upper limbs of young tennis players - Brosseau, O.; Hautier, C.; Rogowski, I. (Medicine and Science in Tennis, 2006)
This study aims to investigate the side-to-side differences in upper limb volumes in young national tennis players using a field method. Fifty-nine tennis players (7-17 years) were described by 24 anthropometric measurements in order to calculate each dominant and non-dominant upper limb volumes, using the truncated cone method. The total volume of the dominant upper limb was 7.8% larger than that of the non-dominant one. Moreover each respective cone of the playing upper limb was greater than that of the non-playing one. The easiness and reliability of the truncated cone method should lead to coaches being able to follow the anthropometric development, and especially the incidence of segmentary volume asymmetry, of their players.